Intraoperative arterial pressure and delayed cerebral ischemia in patients with aneurysmal subarachnoid hemorrhage after surgical clipping: A retrospective cohort study - Wang, Jie; Li, Runting; Li, Shu; Ma, Tingting; Zhang, Xingyue; Ren, Yue; Chen, Xiaolin; Peng, Yuming (Frontiers in Neuroscience, 2023)
Background Delayed cerebral ischemia (DCI) is the major predictor of poor outcomes in patients with aSAH. Previous studies have attempted to assess the relationship between controlling blood pressure and DCI. However, the management of intraoperative blood pressure in reducing the occurrence of DCI still remains inconclusive. Methods All patients with aSAH who received general anesthesia for surgical clipping between January 2015 and December 2020 were prospectively reviewed. Patients were divided in the DCI group or the non-DCI group depending on whether DCI occurred or not. Intraoperative arterial pressure was measured every minute and recorded in an electronic anesthesia recording system along with intraoperative medication and other vital signs. The initial neurological function score, aneurysm characteristics, surgical and anesthetic information, and outcomes were compared between the DCI and the non-DCI groups. Results Among 534 patients who were enrolled, a total of 164 (30.71%) patients experienced DCI. The baseline characteristics of patients were similar between the groups. The World Federation of Neurosurgical Societies (WFNS) Scale > 3, age ≥ 70 years, and the modified Fisher Scale > 2 were significantly higher in patients with DCI than those without. Though it was the second derivative of the regression analysis, 105 mmHg was adopted as the threshold for intraoperative hypotension and was not associated with DCI. Conclusions The threshold of 105 mmHg was adopted as intraoperative hypotension even though it was the second derivative of the regression analysis and could not be proved to be associated with delayed cerebral ischemia adjusted by the baseline severity of aSAH and age.